Problematika Pelaksanaan Kebijakan Otonomi Khusus kepada Daerah Papua dan Papua Barat dengan Perspektif Kebijakan Publik - Jonathan Jacob Paul Latupeirissa; I Putu Darma Wijaya; I Made Yuda Suryawan (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
The concept of special autonomy basically has two objectives: reducing the conflict of separatism and improving welfare from disparities with other regions. The prolonged conflict in Papua has brought several multidimensional adversities which tend to be neglected. The people in Papua experience the most loss. This article aims to analyze the problems with the particular autonomy policy in Papua and West Papua Provinces. The research uses a qualitative approach. Sources of data used come from analysis sourced from various kinds of literature such as books and journals. The description found in this research shows that the implementation of special autonomy has not been effectively and efficiently implemented. Indicators of the success of public services and conflict resolution are still far from concept. To conclude that granting special autonomy cannot necessarily be implemented pragmatically, the government needs to take humanist approaches that prioritize humanity.